The Effectiveness of Reality-Based Group Counseling in Enhancing Open-Mindedness Among Students with Factory Worker Parents - Ramjani Novita Fajar Ningrum; Zakki Nurul Amin (ProGCouns: Journal of Professionals in Guidance and Counseling, 2026)
This study is based on the low level of open-mindedness among students, particularly among students with limited parental support. This study aims to examine the effectiveness of reality-based group counseling in fostering students' open-mindedness whose parents are factory workers. The study employed a quasi-experimental control group time-series design, involving 12 students selected via purposive sampling, who were subsequently assigned to an experimental group (n = 6) and a control group (n = 6). Data were measured repeatedly, at pretest, mid-test, and post-test using an adapted version of the Actively Open-Minded Thinking (AOT-17) instrument, which consists of 17 items. Validity was tested using Product-Moment correlation (r = 0.125-0.669) and reliability via Cronbach's Alpha (r = 0.681). The data obtained were analyzed using Mixed ANOVA to determine differences across the three measurements. The analysis results indicated significant differences after the three measurements in the experimental group post-intervention, with an F(1, 10) = 158.844, p < 0.05, reflected in the pretest mean (M = 50.00) and post-test mean (M = 70.00). The results indicate that the intervention contributed significantly to the change. These findings confirm that the intervention was effective in enhancing open-mindedness; it can be recommended as an effective strategy for counselors. Future researchers are encouraged to examine various background and individual characteristics to gain a more comprehensive understanding.